2016
DOI: 10.1002/anie.201602320
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Electrophilic NH Using Convenient Sources of Ammonia: Direct Synthesis of NH Sulfoximines from Sulfoxides

Abstract: A new system for NH transfer is developed for the preparation of sulfoximines, which are emerging as valuable motifs for drug discovery. The protocol employs readily available sources of nitrogen without the requirement for either preactivation or for metal catalysts. Mixing ammonium salts with diacetoxyiodobenzene directly converts sulfoxides into sulfoximines. This report describes the first example of using of ammonia sources with diacetoxyiodobenzene to generate an electrophilic nitrogen center. Control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
177
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(181 citation statements)
references
References 51 publications
2
177
0
2
Order By: Relevance
“…22 We report herein a direct preparation of NH--sulfoximines from sulfides by using readily available sources of ammonia in the presence of PhI(OAc) 2 . We reasoned that our protocol for NH transfer to sulfoxides 19 could be extended to sulfides to generate the corresponding sulfilimines, by reaction with the electrophilic nitrene intermediate. However, we were both surprised and delighted to find that when sulfide 1a was reacted with 4 equiv of ammonium carbamate (NH 2 COONH 4 ) in the presence of 2.5 equiv of PhI(OAc) 2 in MeOH at 25 °C, exclusive formation of the corresponding sulfoximine 2a was observed (Scheme 2, conditions i).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22 We report herein a direct preparation of NH--sulfoximines from sulfides by using readily available sources of ammonia in the presence of PhI(OAc) 2 . We reasoned that our protocol for NH transfer to sulfoxides 19 could be extended to sulfides to generate the corresponding sulfilimines, by reaction with the electrophilic nitrene intermediate. However, we were both surprised and delighted to find that when sulfide 1a was reacted with 4 equiv of ammonium carbamate (NH 2 COONH 4 ) in the presence of 2.5 equiv of PhI(OAc) 2 in MeOH at 25 °C, exclusive formation of the corresponding sulfoximine 2a was observed (Scheme 2, conditions i).…”
mentioning
confidence: 99%
“…The data reported in Table 1 suggest that two equivalents of oxidant are mandatory to reach full conversion. Based on our previous mechanistic investigation on the direct NH--transfer to sulfoxides, 19 we reasoned that one equivalent of PhI(OAc) 2 would be required to generate the nitrene intermediates (PhI=NH or PhIN + ), whereas the second equivalent would promote the oxygen transfer. To investigate whether N or O is transferred first, we set a series of experiments using diphenyl sulfide derivatives (Scheme 3).…”
mentioning
confidence: 99%
“…Bolm confirmed the ineffective nitrene transfer to phenyl trifluoromethyl sulfide and its corresponding sulfoxide and thus developed a three‐step synthesis of N ‐protected trifluoromethyl sulfoximines . The same tendency was observed by Luisi and Bull during the metal‐free nitrene transfer to 4‐bromophenyl trifluoromethyl sulfoxide . The first synthesis of fluorinated NH ‐sulfoximines was described by Shreeve's group by using sulfur oxydifluorides and ammonia .…”
Section: Methodsmentioning
confidence: 54%
“…In order to investigate whether replacing the sulfone moiety with a sulfoximine improves the antiplasmodial activity of the thiochroman scaffolds, sulfoximines 6a and 6b were prepared as shown in Scheme 1 using the protocol reported by Zenzola et al [30,31] our previously reported protocol, [32] was oxidized using 1.2 equiv. of oxone ® to afford sulfoxides 8a and 8b as a separable mixture in 1:3 diastereoisomeric ratio, while oxidation with excess oxone ® led to the formation of sulfone 5 in reasonable yields (Scheme 1).…”
Section: Synthesis Of Sulfoximine Analogues Of the Sulfone-derived mentioning
confidence: 99%